2022
DOI: 10.1016/j.tvr.2021.200233
|View full text |Cite
|
Sign up to set email alerts
|

The association between viral load and concurrent human papillomavirus infection at the genital and anal sites of young women and the impact of vaccination

Abstract: Concurrent genital-anal human papillomavirus (HPV) infections may impose an increased anal cancer risk in women with HPV-related genital lesions. High viral load may facilitate genital-anal HPV concurrence. Genital and anal HPV is reduced by a bivalent HPV16/18 vaccine, yet the effect on concurrent genital-anal HPV remains unclear. This study analyzed viral load in concurrent genital-anal HPV infections, relative to genital-only and anal-only HPV infections and the impact of vaccination in young wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…3,12 Screening programs for high-risk populations have been proposed, as anal cancer is preventable with a 5-year survival rate of 67% and a risk of metastasis. 2,4,6 Anal cancers have been associated with a history of cervical dysplasia, cervical cancer, and vulvar cancer. An interval of 4-16 years was proposed between the diagnosis of cervical cancer and the occurrence of anal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,12 Screening programs for high-risk populations have been proposed, as anal cancer is preventable with a 5-year survival rate of 67% and a risk of metastasis. 2,4,6 Anal cancers have been associated with a history of cervical dysplasia, cervical cancer, and vulvar cancer. An interval of 4-16 years was proposed between the diagnosis of cervical cancer and the occurrence of anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although no significant association between anal cancer and fissures or hemorrhoids has been found, a prolonged viral infection of anal mucosa is a risk factor for anal dysplasia and cancer. 4,8 HPV infection in the anal mucosa might serve as a reservoir for HPV in cervical reinfection, although no history of anal sex was found in women with a history of cervical infection. 4 The most common viral etiologies in the anal mucosa are HPV16 and HPV18, followed by HPV33 and HPV31.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in sexual practices and risky behavior trends can increase the prevalence of anal STIs in the developed world [ 2 ]. Transmission between the anus and cervix and vice versa are common in women [ 3 , 4 , 5 ]. This aspect needs to be further investigated because the woman may have HPV infection in both sites, genital and anal, at the same time that it is investigated, but which may be of different HPV types acquired in different exposures in life.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect needs to be further investigated because the woman may have HPV infection in both sites, genital and anal, at the same time that it is investigated, but which may be of different HPV types acquired in different exposures in life. The genital site is likely the main source of a concurrent genital–anal HPV infection, which is well mentioned in the scientific literature [ 4 ], but it is a hypothesis supported by studies with limitations [ 6 ]. Concordance studies between genital and anal infections and the HPV genotypes identified between the two sites can bring clearer answers if they use more robust methodological approaches for HPV detection and genotyping, as well as statistics with better robustness [ 6 ].…”
Section: Introductionmentioning
confidence: 99%